The Effect of Ascorbic Acid Supplementation on the Time of Healing of Rats Submitted to Neurosurgical Procedures - Rosa, Tiago Gonçalves (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Vitamin C is an essential nutrient for both humans and rats and has been noted for its beneficial properties, among them, healing.Objective To verify the effect of oral and subcutaneous vitamin C supplementation on the healing time of surgical wounds of rats skulls.Statistical Methodology Thirty male Wistar rats were divided into 3 groups: 10 from the control group (GI), 10 from the group treated with oral vitamin C (GII), and 10 from the group treated with subcutaneous vitamin C (GIII). Vitamin C was administered to GI and GIII animals from the 3rd to the 7th postoperative day, totaling 10 days of administration at a dose of 100 mg/kg/day. On the 4th day of the study, the rats were submitted to a surgical procedure consisting of a 2-cm incision of the skin of the animals' heads and suturing with single stitches. After a determined period, the rats were killed and submitted to the collection of material for study by the picrosirius red technique for the evaluation of collagen types I and III, the degree of hematoxylin and eosin healing, and the rate of contraction of the wound on subsequent days. The results were described in averages, medians, minimum and maximum values, and standard deviations. For the comparison of the three groups, the analysis of variance with one factor (one-way ANOVA) or Kruskal-Wallis non-parametric test was used. The normality of the variables was evaluated by the Shapiro-Wilk test. Values of p < 0.05 indicated statistical significance. The data were analyzed using the IBM SPSS Statistics for Windows, v.20.0. software. (IBM Corp., Armonk, NY, USA).Results The amount of collagen type III was higher in the groups that received vitamin C, however, without significant difference (n = 0.292). In relation to the rate of contraction of the surgical wound, it was higher in the groups treated with vitamin C, with a significant difference between groups I and II (p = 0.001), and between groups I and III (p < 0.001). No significant difference was found between the groups that were treated with vitamin C (p = 0.227).Conclusion Healing was more effective in the groups treated with vitamin C than in the group that did not receive vitamin supplementation. There was no significant difference in healing between the groups receiving oral or subcutaneous vitamin C.
Keywords: scalp; healing; ascorbic acid; Wistar rats